Viability of Bifidobacterium bifidum 1 under hypothermia, single and repeated freeze-thaw cycles. - Knysh, Oksana; Pakhomov, Oleksandr; Kompaniets, Antonina; Polianska, Valentina; Zachepylo , Svitlana (Problems of Cryobiology and Cryomedicine, 2020)
Abstract: The viability of bacteria of the Bifidobacterium bifidum 1 probiotic strain under hypothermia, single and repeated freeze-thaw cycles (thermal cycling) was studied. Samples of bifidobacterial suspensions were frozen immediately after isolation or after daily hypothermic storage in three ways to the final temperature of either (–23 ± 1) or (–196 ± 1)ºC. After slow freezing of the samples down to (–23 ± 1) ºC bigger quantitative losses of bifidobacteria were observed if compared with those after rapid freezing by a direct immersion into liquid nitrogen. Storage of the samples under hypothermia and a single freeze-thaw was accompanied with a strong inhibition of the daily growth of bifidobacteria biomass and an increased formation of biofilms. Ten-fold thermal cycling in the most unfavorable way for survival did not lead to the death of all cells in suspensions. Up to 35% of bifidobacteria remained viable. Indices of the bifidobacteria ability to enhance biomass remained at the level of 35%, and the ability to form biofilm was kept at the level of 43.7–65.5% of the corresponding indices for freshly isolated cells. Probl Cryobiol Cryomed 2020; 30(3): 247–255